Glyphosate loss by runoff and its relationship with phosphorus fertilization - Sasal, Maria Carolina (2015)
The aim of this study was to evaluate the relationship between glyphosate and phosphate fertilizer application and their contribution to surface water runoff contamination. The study was performed in Aquic Argiudoll soil (Tezanos Pinto series). Four treatments were assessed on three dates of rainfall simulation after fertilizer and herbicide application. The soluble phosphorus in runoff water was determined by a colorimetric method. For the determination of glyphosate and aminomethylphosphonic acid (AMPA), a method based on fluorenylmethyloxycarbonyl (FMOC) group derivatization, solid phase extraction (SPE) purification, and ultrahigh-performance liquid chromatography−tandem mass spectrometry (UHPLCMS/MS) was employed. The application of phosphorus fertilizer resulted in an increased loss of glyphosate by runoff after 1 day of application. These results suggest the need for further study to understand the interactions and to determine appropriate application timing with the goal of reducing the pollution risk by runoff.